POLICY OF INDRAGIRI HILIR REGENCY LOCAL GOVERNMENT IN SOLOP ECOTOURISM DEVELOPMENT IN 2018 - M. Hadi; M. Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Solop Ecotourism Area is one of the leadest tours in Indragiri Hilir Regency, which is a tourism concept that utilizes local resources by connecting amongst natural tourism trips that have vision and mission of conservation and environment love. The other, the concept of ecotourism is also directed to maintaining local culture. Solop ecotourism is jointly managed by Indragiri Hilir Regency Local Government with Pulau Cawan Village. The budgeted funds for Solop Ecotourism that are still very minimal, which is causing the development of the area and the procurement of facilities and infrastructure that must be going through a priority scale. This study aims to determine the policy of Indragiri Hilir Regency Local Government in developing Solop Ecotourism in 2018. The type used in this study is descriptive research with a qualitative research approach. The types of research data are primary data and secondary data. Data collection techniques in this study are interview and documentation. Technical data analysis used is qualitative descriptive data analysis. Based on the results of the study, policies carried out by Indragiri Hilir Regency Local Government in developing Solop Ecotourism are as follows; 1) Promoted and reintroduced by rebranding Solop Beach tours into Ecotourism Solop; 2) Synergize with the Cawan Island Village Government; 3) Encourage the development of facilities and infrastructure to support the development of Solop Ecotourism; 4) Issue Decrees that related to Solop Ecotourism (Destination Decree and Tourist Attraction Decree); 5) Conduct socialization and training on tourism and empowerment of communities around the Solop Ecotourism area; 6) Hold events in the Solop Ecotourism area. There are factors that influence the policy of Indragiri Hilir Regency Local Government in developing Ecotourism in Solop that:: 1) Internal factors: Local government policy in the form of Local Regulation regarding Solop Ecotourism development doesn’t exist, Lack of human resources, lack of budget, and lack of facilities (facility and infrastructure). 2) External factors: Far from location, and accessibility that is difficult to reach to the Solop Ecotourism area.Keywords: Local Government, Policy, Ecotourism